2017
DOI: 10.2147/ott.s151800
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 promotes nasopharyngeal carcinoma progression through regulation of miR-124/NF-κB pathway

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most common malignancies and seriously endangers people’s health. Recently, long noncoding RNA (lncRNA) NEAT1 has been determined as an oncogenic gene in a variety of cancers. However, the effect of NEAT1 in NPC and its underlying mechanism have not been well elaborated. In this study, the data showed that NEAT1 was upregulated and miR-124 was downregulated in NPC tissues and cells. Loss-of-function revealed that NEAT1 knockdown inhibited proliferation and promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 35 publications
(39 reference statements)
0
45
0
Order By: Relevance
“…For example, NEAT1 was reported to sponge miR-101 in non-small cell lung cancer [34], papillary thyroid carcinoma [35], hepatocellular carcinoma [36] and breast cancer [11]. Besides, NEAT1 sponged miR-124 in neuroblastoma [37], retinoblastoma [38], Alzheimer's disease [38] and nasopharyngeal carcinoma [39]. Furthermore, NEAT1 sponged miR-129 in esophageal squamous cell carcinoma [40] and hepatoblastoma [41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, NEAT1 was reported to sponge miR-101 in non-small cell lung cancer [34], papillary thyroid carcinoma [35], hepatocellular carcinoma [36] and breast cancer [11]. Besides, NEAT1 sponged miR-124 in neuroblastoma [37], retinoblastoma [38], Alzheimer's disease [38] and nasopharyngeal carcinoma [39]. Furthermore, NEAT1 sponged miR-129 in esophageal squamous cell carcinoma [40] and hepatoblastoma [41].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-NEAT1 functions as a ceRNA of miRNAs, which plays an important regulatory role in cancer by antagonizing miRNAs functions and modulating miRNAs targets. 20 For example, lncRNA-NEAT1 promotes cell growth and invasion through miR-211/HMGA2 axis in breast cancer. 36 Here, miR-124 was identified as a target of lncRNA-NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 LncRNAs can regulate the expression of target mRNAs by acting as molecular sponges for miRNAs, thereby influencing the development of tumor. 18,19 Cheng et al 20 have reported that lncRNA-NEAT1 promotes the progression of nasopharyngeal carcinoma by regulating miR-124/Nuclear factor-κB (NF-κB) pathway. However, the interaction between lncRNA-NEAT1 and miR-124 in CC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…another study showed that neaT1 regulates the mir-107-mediated expression of cyclin-dependent kinase 6 in laryngeal squamous cell cancer (32). a number of studies have demonstrated that the expression of NEAT1 can be activated by NF-κB and p53, and activate PI3K/AKT pathways (33)(34)(35). However, the function of neaT1 in the pathogenesis of glaucoma has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…When oxidative stress occurs, PI3K/Akt, NF-κB and p53 signaling pathways are directly activated by roS, thus causing damage to ocular structures (7,9). The roS regulate lncrnas, and some lncRNAs influence these pathways (33)(34)(35)(36)(37)(38)(39)(40). a total of 70 differentially expressed lncrnas were obtained, of which 24 participate in the lncrna-mirna-mrna interaction network.…”
Section: Discussionmentioning
confidence: 99%